High-precision neural information detection of multiple brain regions in mice under different concentrations of isoflurane anesthesia based on microelectrode arrays - Yiming Duan; Qianli Jia; Jinping Luo; Yu Wang; Qi Li; Shiya Lv; Luyi Jing; Wei Xu; Xiaoying Zhang; Yulong Ma; Weidong Mi; Xinxia Cai (Microsystems & Nanoengineering)
Abstract The precise neural mechanisms by which general anesthetics induce unconsciousness remain undetermined, with ongoing debate over whether they primarily affect the cortex directly or act predominantly on the sleep–wake brain regions. There is an urgent need for high-precision methodologies to detect and analyze neural information across cortical and subcortical regions. In this study, we designed and fabricated the microelectrode arrays to detect electrophysiological signals from nine brain regions, ranging from the secondary motor cortex to the preoptic area in mice under different concentrations of isoflurane anesthesia. The results demonstrate that isoflurane induces a synchronous inhibitory effect on neural activity in both cortical and subcortical regions of mice during the maintenance phase of anesthesia, which intensifies with increasing anesthesia concentration. Moreover, cortical neurons exhibit a more pronounced inhibitory response to isoflurane, as reflected by significant reductions in local field potential power and spike firing rates compared to subcortical neurons during the suppression phase. These findings suggest that isoflurane during the maintenance phase of anesthesia is more likely to align with the “top–down” paradigm by directly inhibiting cortical regions to maintain unconsciousness. In summary, these discoveries could further refine the study of the neural mechanisms of isoflurane-induced unconsciousness.